APLIKASI MODIFIKASI VARIAN “BIOTIN” UNTUK PENGHIJAUAN DAN TANAMAN OBAT KELUARGA DI KELURAHAN BERKAS, KOTA BENGKULU - Eko Sumartono; Merlian Zikri; Basuki Sigit Priyono (DHARMA RAFLESIA, 2018)
Consequences that arise as population growth and negative paradigm about fecal waste become one of unhealthy residential factors. However, if managed properly and correctly it can improve the welfare of the community. The management of biotic waste (biotin) into biotic and biococopit variations can be used to optimize the utilization of waste management. The management of this activity aims to cultivate environmental awareness, self-sufficiency of food and medicine, and optimization of narrow land use. The results to be achieved in this activity is community empowerment urban village Berkas is to improve the ability and skills of housewives in managing biotin variation as an effort to green the yard, coastal and family medical plants. Socialization is the initial stage of community empowerment. Counseling and training are the methods applied to this activity through personal and group approaches. Socialization is done by introducing variation of planting medium, plant type, and crop management. Meanwhile, the training that was carried out was planting, care and crop management. Optimization of narrow space utilization by utilizing biotin variation is expected to create a society with self-sufficient conditions of food and medicine. In addition, biotin variations become a new resource in the utilization of waste in the environment around urban village Berkas. Keywords: empowerment, biotin, self-sufficient food, medicine plant